Modellvorstellungen zur räumlichen Verteilung von Spurenmetallverunreinigungen in der Bundesrepublik Deutschland, angezeigt durch den Metallgehalt in epiphytischen Moosen - Hermann, Reimer (ERDKUNDE, 1976)
Samples of the epiphytic moss Hypnum cupressiforme L. ssp. filiforme Brid. were gathered at the regularly distributed nodes of two grids laid randomly over the Federal Republic of Germany. The concentrations of Be, Cd, Cu, Ni, Pb and Zn in the organic material were determined by atomic absorption spectrophotometry. Maps showing the regional variation of these trace metal concentrations, as well as their interconnections disclosed by a principal component analysis, reveal high intercorrelations of Cd, Cu,Pb and Zn whereas Ni and Be behave each in a different manner. A multidimensional discriminant analysis shows that the regional distribution of the trace metals may be explained by the distance to the next nonferrous metal smelter and variables which describe the economic structure. From maps showing the regional variation of a single trace metal and from a map prepared by a cluster analysis, which serves too to distinguish between typical groups of trace metal combinations, it can be seen that the highest trace metal deposits occur in the industrial area of Rhine and Ruhr and the northern Harz mountains, whereas the lowest occur in Lower Bavaria and parts of northern Germany.